Spectral degree of linear polarization and neutral points of polarization in snow and ice surfaces. (October 2021) - Tanikawa, Tomonori; Masuda, Kazuhiko; Ishimoto, Hiroshi; Aoki, Teruo; Hori, Masahiro; Niwano, Masashi; Hachikubo, Akihiro; Matoba, Sumito; Sugiura, Konosuke; Toyota, Takenobu; Ohkawara, Nozomu; Stamnes, Knut
Highlights: Angular dependence of spectral degree of linear polarization (DoLP) and its related Stokes parameters Pq (=- Q / I ) and Pu (= U / I ) of Stokes vector I S =[ I Q U V ] T was measured for various snow and ice surfaces. The existence of neutral points of Pq and Pu in the snow and ice surfaces was revealed for the first time. The angular dependence of the neutral points in the shortwave infrared regions was linked exclusively to the measurement geometry regardless of snow particle size, shape and scattering/absorbing inclusions in the ice. Abstract: The properties of light reflected from snow and ice surfaces are important for the understanding of light scattering theory and the interpretation of remote sensing in the cryosphere. Spectral measurements of the degree of linear polarization (DoLP) and its related Stokes parameters P q = − Q / I and P u = U / I of Stokes vector I S = [ I Q U V ] T were made for various snow and ice surfaces in Hokkaido, Japan. The measurement results indicated that the angular dependence on both the viewing angle and azimuth angle in the DoLP, P q and P u was significant especially in the shortwave infrared (SWIR) regions. In addition, an important finding here is that the measurements revealed for the first time the existence of neutral points of P q and P u in the snow and bare ice surface. The SWIR polarization features can be explained by the single scattering properties of snow/ice or surface reflection associated with surface scattering. For the snow cases, the DoLP was represented by the measurement geometry and the scattering phase matrix while for the bare ice case, the DoLP was represented by the measurement geometry and the Fresnel reflection matrix. An additional remark is that the angular dependence of the neutral points was linked exclusively to the measurement geometry regardless of snow particle size, shape and scattering/absorbing inclusions in the ice. In contrast, the polarization in the visible regions was so small but remained detectable. However, the angular dependence of the neutral points was somewhat different from that in near infrared and SWIR regions. These results suggested that the neutral points depend on the polarization magnitude and the plane of polarization that related to the multiple scattering in the snow and atmosphere. The polarimetric measurements related to the neutral points are expected to be useful for the retrieval of new snow/ice physical parameters.